The importance of crown cover on the sustainability of cork oak stands - Ribeiro, Nuno de Almeida (2004)
The cork oak (Quercus suber L.) production system in Portugal, referred to as montado, occupies 713,000 ha representing 22% of Portugal’s forest area. In the last 5 decades several changes occurred in the forest management of cork oak stands, mainly due to the reduction of hand labour and increasing mechanization, creating a new set of risk factors to production system sustainability. Of all risk factors, soil loss, crown cover reduction and lack of regeneration are responsible for the degradation processes in the montado system. in the present work a simulation study on the sustainability (ecological and economical) of cork oak stands at a regional level is presented. The ecological sustainability is classified by a soil erosion index based on the Universal Soil Loss Equation, and the economical one is evaluated by cork production index based on cork quantity and quality. The simulations are preformed using a tool named “CORKFITS 2.1” which is a single-tree spatial growth simulator decision support system (DSS), integrated with GIS geoprocessing and spatial analysis tools in order to produce maps at regional level. The results indicate that crown cover controls the erosion risk index, especially in the areas where the slope exceeds 15%. The sustainability depends on the maintenance of crown cover, which can be achieved by low intensity regeneration process every 20 years.